General Scientific Basics of Pedagogical History Researches - Holubnycha, Liudmyla; Besarab, Tetiana (Educational Challenges, 2021)
The manuscript presents general scientific basics of researches on history of pedagogy. They are connected with methodology and historiography. As studying history of any science is always significant because it helps to clarify the state of the problem under research as well as contributes to improving the scientific level of the author's investigation it is very important to make this investigation in a proper methodological way in order to avoid errors in the work of the researcher. Thus, the paper is topical. The purpose of the article is to determine the methodology of historiographical investigation of researches on history of pedagogy. The objectives of the study are to clear up the methodological principles of the mentioned research, methods of their knowledge and means of historiographical research in this area. The methodology used in the study is presented by general theoretical methods such as analysis and synthesis of related researches together with narrative method. They helped to receive and present the results as well as to make the conclusion. The results of the study show that any research of the historiography of pedagogical history should be based on scientific methodology. Tools for such researches are methodological principles (historicism, systematics, objectivity, comprehensiveness, and continuity), methods (analysis, synthesis, methods of typology and comparison, as well as bibliographic method) and means of knowledge (information technology, computers, office equipment, information computing devices). The conclusions allow asserting that mastering the methodological tools is a necessary condition for improving the scientific level of historiographical research on the history of pedagogy.